Vallás- és lelkiismereti szabadság az ókori Rómában - Grüll, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
It is widely believed that the Roman Empire, as a polytheistic society, was basically tolerant of different religions. This is largely true, but the Romans divided religious phenomena into two categories: religio meant ‘normal’ religion approved by the state authorities, and superstitio meant ‘deviant’ religious phenomena considered harmful by the state and dangerous to society. The latter was also tried to be restricted by the law. The Romans included Judaism, which had already appeared on the Italian peninsula from the 2nd century Bc, although it was almost completely opposed to the pagan religions, among the religions and ensured its free practice by means of ‘positive discrimination’. In contrast, Christianity, which emerged in the mid-1st century Ad, was classified as superstitio at the moment of its appearance, and was not only rendered legally impossible, but also subjected to physical persecution. Christian apologists, especially the legally skilled Tertullian, did their utmost to convince the Romans that Christianity was worthy of the name religio. The Carthaginian author not only introduces the concept of ‘religious freedom’ but also argues that Christianity is worthy of freedom on the basis of the Stoic idea of ‘conscience’ and the ius naturale.